PROPERTY LIABILITY OF THE GOVERNING BODIES OF A LEGAL ENTITY - Tolstova, Irina; Kokorev, Alexander; Vasilyevich Gaidashov, Alexander; Kovshevatsky, Vladislav (Revista Inclusiones, 2020)
The article analyzes the problems of bringing members of the governing bodies of a legal entity to property liability under the legislation of the Russian Federation and in international practice. The purpose of this work is to consider in detail the features of bringing the governing bodies of a legal entity to civil liability. Corporate relations involving legal entities of various organizational and legal forms in the Russian Federation have emerged and have been developing relatively recently. Thus, various aspects of these relations, such as the property liability of their participants, including the governing bodies of a legal entity, are not fully regulated. The lack of regulation negatively affects the activities of organizations and the protection of the rights of their participants and creditors, creates conditions for abuse, and requires the constant attention of the legislator to them to protect the legitimate interests of all participants in the above-mentioned relations.